BRCA mutations in pancreatic cancer and progress in their targeting. (3rd July 2021) - Alkassis, Samer; Yazdanpanah, Omid; Philip, Philip Agop
ABSTRACT: Introduction : Genomic instability resulting from DNA damage repair (DDR) deficiencies is a hallmark of cancer and offers treatment opportunities. Homologous recombination DDR defect is a result of multiple critical gene mutations, including BRCA1/2 . Targeting DNA DDR defects in pancreatic cancer (PC) is emerging as a potential treatment strategy with current focus on BRCA mutations. Areas covered : Challenges in treating patients with PC are explained. We review DDR defects as a treatment target in PC, specifically, germline BRCA mutation and sensitivity to platinum compounds and exploiting the strategy of synthetic lethality using poly (ADP-ribose) polymerase (PARP) inhibition. Literature review was undertaken through PubMed, Google Scholar, and Clinicaltrials.gov website. Expert opinion : DDR defects are promising targets for novel therapies in PC. Early application of such strategy is in patient subgroup with BRCA germline mutation, which is seen in only 5–7% of the PC population. The oral PARP inhibitor olaparib in the maintenance setting represents the first targeted therapy in metastatic PC based on a phase 3 study. There is a very modest benefit for patients with PC using PARP inhibitors. Future work must improve our understanding of mechanisms of sensitivity and resistance to PARP inhibitors in PC and enhance the molecular selection of patients for such therapy.